2010
DOI: 10.1038/onc.2010.120
|View full text |Cite
|
Sign up to set email alerts
|

LSD1-mediated demethylation of histone H3 lysine 4 triggers Myc-induced transcription

Abstract: Myc is a transcription factor that significantly contributes to cancer progression by modulating the expression of important genes through binding to a DNA sequence, CACGTG, called E-box. We find that on Myc binding to chromatin, the lysine-demethylating enzyme, LSD1, triggers a transient demethylation of lysine 4 in the histone H3. In addition, we demonstrate that Myc binds and recruits LSD1 to the E-box chromatin and the formation of this complex is stimulated by cAMP-PKA. Demethylation by LSD1 produces H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(175 citation statements)
references
References 41 publications
6
164
1
Order By: Relevance
“…Currently, there are 2 known classes of histone demethylases: the Flavin-dependent histone demethylases and the Jumonji-containing histone demethylases. The first class, containing lysine-specific histone demethylase 1 and 2 (LSD1, 2), is involved in modulating gene expression through demethylation of either mono-or di-methyllysine residues of H3K4 [38][39][40][41] or H3K9 [42][43][44] resulting in gene repression or gene activation, respectively. 45 During this histone demethylation process, H 2 O 2 is produced, 46 which has been proposed to be involved in signaling processes.…”
Section: Dnmt-3a and -3b As Demethylating Enzymes: Implicationsmentioning
confidence: 99%
“…Currently, there are 2 known classes of histone demethylases: the Flavin-dependent histone demethylases and the Jumonji-containing histone demethylases. The first class, containing lysine-specific histone demethylase 1 and 2 (LSD1, 2), is involved in modulating gene expression through demethylation of either mono-or di-methyllysine residues of H3K4 [38][39][40][41] or H3K9 [42][43][44] resulting in gene repression or gene activation, respectively. 45 During this histone demethylation process, H 2 O 2 is produced, 46 which has been proposed to be involved in signaling processes.…”
Section: Dnmt-3a and -3b As Demethylating Enzymes: Implicationsmentioning
confidence: 99%
“…Here, we also noted that synergistic activity of cotreatment with SP2509 and PS was associated with a greater depletion of c-Myc expression in the primary AML blast progenitor cells expressing mutant NPM1. While other reports have shown that combined inhibition of LSD1 and HDACs achieves superior anti-tumor activity against glioblastoma and breast cancer cells (43,44), in these reports, the LSD1 Fiskus et al Page 10 antagonists employed are known to be either irreversible LSD1 inhibitors (45), or exhibit intolerable in vivo activity in the mouse models of AML where these inhibitors were studied (17,18). In contrast, our in vivo studies demonstrate that co-treatment with SP2509 and PS yields significantly better survival without inducing toxicity, and suggests a potential for cure of the immune-depleted mice engrafted with AML cells expressing NPM1 mutation irrespective of the co-expression of FLT3-ITD.…”
Section: Sp2509 Is a Small Molecule Reversible Inhibitor Of Lsd1 (19)mentioning
confidence: 99%
“…Although a large body of literature is devoted to the appearance of epigenetic methylation marks in DNA, much less is known about their removal. It has been recently shown that oxoGua, one of the most widespread oxidative DNA lesions, is a key element in the gene activation by ERα (Perillo et al, 2008) and c-Myc transcription factors (Amente et al, 2010). This damage is removed from DNA by DNA glycosylase OGG1 and AP endonuclease APEX1, and the nicks appearing in DNA ultimately lead, through a still unknown mechanism, to local chromatin decondensation and transcription activation.…”
Section: Structural Insights Into the Mechanism Of Homologous Recombimentioning
confidence: 99%